Liquid-Liquid extraction of aromatics and sulfur compounds from base oil using ionic liquids - Al Kaisy, G.M.J. (Elsevier Ltd, 2016)
The viability of using ionic liquids (ILs) as extractive solvents to remove naphthalene (aromatics) and dibenzothiophene (DBT; Sulfur) from base oil by liquid-liquid extraction was investigated. The experiments were designed using Response Surface Methodology (RSM) with 1-butyl-3-methylpyridinium dicyanamide BMPYDCA, 1-butyl-3-methylimidazolium dicyanamide BMIMDCA, 1-butyl-3-methylimidazolium thiocyanate BMIMSCN and 1-butyl-3-methylimidazolium dimethylphosphate BMIMDMP ILs. The sulfur compound and aromatics were analyzed using Total Sulphur analyzer and High Performance Liquid Chromatography (HPLC) with high coefficient of determination i.e. R2 values of 0.964 and 0.997 respectively. The effects of different ILs, temperatures, and ILs to oil mass ratio (IL:Oil) were optimized.BMPYDCA appeared as the most promising medium with 94.3% of dibenzothiophene and 83.1% of naphthalene removal after a single extraction step. The aromatics and sulfur removal efficiency of BMPYDCA IL was 54.3%, 78.3% and 82.9%, 93.8% at IL:Oil ratios of 0.4 and 1.8, respectively. An increase in temperature did not improve the extraction efficiency, but a slight decrease was noted.Results emphasized that extraction of aromatics and sulfur compoundsfrom base oil can be achieved successfully using selected ionic liquids. Â© 2016 Elsevier Ltd.